Lactate/Albumin Ratio as a Predictor of In-Hospital Mortality in Septic Patients Presenting to the Emergency Department - Bou Chebl, Ralphe; Jamali, Sarah; Sabra, Mohamad; Safa, Rawan; Berbari, Iskandar; Shami, Ali; Makki, Maha; Tamim, Hani; Abou Dagher, Gilbert (Frontiers in Medicine, 2020)
Background: The aim of this study is to evaluate the prognostic value of the Lactate to Albumin (L/A) ratio compared to that of lactate only in predicting morbidity and mortality in sepsis patients. Methods: This was a single-center retrospective cohort study. All adult patients above the age of 18 with a diagnosis of sepsis who presented between January 1, 2014 and June 30, 2019 were included. The primary outcome was in-hospital mortality. Results: A total of 1,381 patients were included, 44% were female. Overall in-hospital mortality was 58.4% with the mortalities of sepsis and septic shock being 45.8 and 67%, respectively. 55.5% of patients were admitted to the intensive care unit. The area under the curve value for lactate was 0.61 (95% CI 0.57–0.65, p < 0.001) and for the L/A ratio was 0.67 (95% CI 0.63–0.70, p < 0.001). The cutoff generated was 1.22 (sensitivity 59%, specificity 62%) for the L/A ratio in all septic patients and 1.47 (sensitivity 60%, specificity 67%) in patients with septic shock. The L/A ratio was a predictor of in-hospital mortality (OR 1.53, CI 1.32–1.78, p < 0.001). Conclusion: The L/A ratio has better prognostic performance than initial serum lactate for in-hospital mortality in adult septic patients.